The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1186/2193-1801-2-58
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of primary brain tumors in childhood and adolescence in Kuwait

Abstract: The relatively high frequency of primary brain tumors (PBT) observed in childhood and adolescence in Kuwait has necessitated this epidemiological study. It is based on the records of the Department of Pathology, Al-Sabah Hospital, which examined all brain tumor biopsies done in this age group in Kuwait between 1995 and 2011. During this period, 75 boys (49%) boys and 77 (51%) girls had histologically confirmed PBT. They comprised 122 children (0–14 years) and 30 adolescents (15–19 years). The boys/girls ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
16
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 27 publications
10
16
3
Order By: Relevance
“…This slight prevalence of males over females reflects the gender distribution of the population at risk, the same was found in a Kuwaiti study [13], where male slight preponderance was reported. In another study [14], where the male-tofemale ratio was 1:3, indicated that the pediatric brain tumors were more prevalent in males than in females and other studies found that too [1,15,18].…”
Section: Discussionsupporting
confidence: 54%
“…This slight prevalence of males over females reflects the gender distribution of the population at risk, the same was found in a Kuwaiti study [13], where male slight preponderance was reported. In another study [14], where the male-tofemale ratio was 1:3, indicated that the pediatric brain tumors were more prevalent in males than in females and other studies found that too [1,15,18].…”
Section: Discussionsupporting
confidence: 54%
“…[152324] The incidence of pilocytic astrocytoma was 16.6% which is much lower than a study by Katchy et al where these tumors constituted 29% of all pediatric brain tumors. [24] Resection is usually incomplete in diffuse astrocytomas due to permeative margins. Limited field external beam irradiation or stereotactic irradiation is the treatment of choice.…”
Section: Discussionmentioning
confidence: 96%
“…9 Of the 60 cases of CNS tumors studied, most tumors (88.3%) were recorded in the age range of 21 to 60 years with peak in the age group of 41-50 years and a mean age of 46.5 years. Katchy et al (2013) found 63 % of the brain tumors in the age group 20 -64 years. 10 The presenting symptoms of CNS tumors are headache, nausea, vomiting, seizure, decreased vision, decreases hearing, changes in behaviour or personality, speech difficulties, gait disturbance, weakness of limbs and changes of sensation.…”
Section: Discussionmentioning
confidence: 95%
“…Katchy et al (2013) found 63 % of the brain tumors in the age group 20 -64 years. 10 The presenting symptoms of CNS tumors are headache, nausea, vomiting, seizure, decreased vision, decreases hearing, changes in behaviour or personality, speech difficulties, gait disturbance, weakness of limbs and changes of sensation. States(CBTRUS) statistical report 2012 the most common site of brain and CNS tumors was meninges(34%) followed by the cerebral lobes (22%).…”
Section: Discussionmentioning
confidence: 95%